Systematic energy and exergy assessment of a hydropurification process: Theoretical and practical insights. (15th January 2022) - Azarpour, Abbas; Mohamadi-Baghmolaei, Mohamad; Hajizadeh, Abdollah; Zendehboudi, Sohrab
Abstract: Improvement of process efficiency and reduction of operation costs are of significant importance in industrial chemical plants. In this study, an effective approach is proposed to analyze a hydropurification process, focusing on energy utilization, operating costs, environmental impact (e.g., CO2 emissions), and exergy performance. The hydropurification process includes heat exchangers, pumps, crystallizers, reactor, and furnace. This process is operated under high pressures and temperatures; it is prone to high consumption of energy and considerable loss of work quality. The vital operating parameters affecting the system performance are chosen by employing Taguchi method. The process simulation and/or thermodynamic modeling are carried out using Aspen Plus® software, and by writing codes for the exergy calculation in MATLAB software environment. The results are in acceptable agreement with the industrial data. The optimal conditions lead to 15% reduction in the process exergy destruction. The optimal operation can be established by implementing lower minimum approach temperature (Δ T min ) of the reaction system feed preheaters (e.g., 5 °C), setting a higher operating pressure in the heat exchangers of the feed preparation section (e.g., 96 bar), and enhancing the performance of heat exchangers using oil as heat transfer medium (optimizing furnace operating conditions). Furthermore, the performance of the fourth and sixth heat exchangers can be enhanced by 33.3%; the performance of the fourth crystallizer can be improved up to 18.7%. The furnace, which utilizes the expensive Therminol® 66 (as the heat transfer fluid), experiences a significant exergy destruction due to significant fluctuations in temperature and thermodynamic irreversibility in the combustion process. Implementation of the proposed optimal conditions can lower the operation costs and carbon tax by 9.96% ($20.5/h) and 14.75% ($14.54/h), respectively; and the CO2 emission rate can be decreased by 0.582 t/h. A decrease in Δ T min of the heat exchangers improves the process specific energy consumption and exergy destruction. Moreover, effective control of the plant and avoidance of high fluctuations in the process parameters can lead to exergy destruction reduction. Highlights: Energy and exergy analysis of an industrial hydropurification process is performed. Process equipment with substantial sources of irreversibility are identified. Process operation at optimal conditions causes 15% decline in exergy destruction. Effective energy-exergy strategy leads to 13.97 t/d reduction in CO2 emissions. Optimal scenario can result in a significant decrease of 9.96% in the operation costs.